2000
DOI: 10.1007/s005200050023
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional measure of religious involvement for cancer patients: the Duke Religious Index

Abstract: Despite increasing interest in the relationship between religious involvement and health outcomes for cancer patients, research has been limited by the lack of appropriate measures. Few of the many instruments available are well suited to cancer patients. The current study examined the psychometric properties of one recently developed measure, the Duke Religious Index (DRI), which assesses several aspects of religious involvement. The DRI was evaluated in two distinct samples: 104 cancer patients receiving tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 49 publications
(42 reference statements)
2
23
0
1
Order By: Relevance
“…Their results showed a Cronbach's alpha of 0.91 and 0.78, respectively. And, in 2000 while evaluating patients with cancer (most with multiple myeloma) and a gynecological sample, Sherman et al (2000) found Cronbach's alpha of 0.90 and 0.87, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Their results showed a Cronbach's alpha of 0.91 and 0.78, respectively. And, in 2000 while evaluating patients with cancer (most with multiple myeloma) and a gynecological sample, Sherman et al (2000) found Cronbach's alpha of 0.90 and 0.87, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, people "use" their religions, whereas intrinsic religiosity is inner motivated and internalized, so that people "live" their religions and try to live according to the beliefs and prescriptions of their religions. Accordingly, spirituality in this study is measured with DRI (Duke Religion Index) [18], which is a strongly accepted instrument to measure religiosity (both extrinsic and intrinsic religiosity) [18][19][20], especially for high reliability and validity though we would concede and state a lack of sophisticated differentiations. The DRI consists of five items; three of them measure the intrinsic religiosity through an ordinal scale (5-Likert Scale).…”
Section: Design and Methods Of The Studymentioning
confidence: 99%
“…Using other conceptualisations of religiosity a positive association with purpose in life was reported by the following studies: Gladding, Lewis, and Adkins (1981) using their own scale of religiosity among 350 students; Paloutzian and Ellison (1982) using their Spiritual Wellbeing Scale among 206 students; Jackson and Coursey (1988) using a measure of church attendance among 98 black Baptists; Richards (1991) using a measure of intensity of prayer experience among 345 participants in a nondenominational programme; Carroll (1993) using an index of spiritual practices among 100 members of Alcoholics Anonymous; Gerwood, LeBlanc and Piazza (1998) using an index of spiritual satisfaction among 130 senior citizens; Sherman, Plante, Simonton, Adams, Harbison, and Buris (2000) using the Duke Religious Index among 104 cancer patients and 175 gynaecology patients; Piedmont and Leech (2002) using their Spiritual Transcendence Scale among 369 students in India; Litwinczuk and Groh (2007) using the Spiritual Involvement and Beliefs Scale Revised (Hutch, Burg, Naberhaus, & Hellmich, 1998), among 46 HIV-positive men and women; Piedmont (2007) using the Spiritual Transcendence Scale among 622 Filipino adults; Ciarrocchi and Brelsford (2009) using the Faith Maturity Scale (Benson, Donahue, & Erickson, 1993) among 602 participants in a general population study; Piedmont, Ciarrocchi, Dy-Liacco, and Williams (2009) using their own Religious Involvement Scale among 467 college students; Dy-Liacco, Piedmont, Murray-Swank, Rodgerson, and Sherman (2009) using a four-item index of religiosity among a convenience sample of 654 Filipino nationals; and Halama, Martos, and Adamovová (2010) using the short-form Francis Scale of Attitude toward Christianity (Francis, Lewis, Philipchalk, Lester, & Brown, 1995) among 274 students in Slovakia and 249 students in Hungary.…”
Section: Explicit Religion and Purpose In Lifementioning
confidence: 99%